Piperine Levels in Java Chili and Black Fruits Extracts from Regions with Different Altitude - Hikmawanti, Ni Putu Ermi; Hanani, Endang; Maharani, Shintia; Putri, Ajeng Istiningtyas Wahyudi (Jurnal Jamu Indonesia, 2021)
Piper retrofractum Vahl. (java chili or cabe jawa) and Piper nigrum L. (black pepper or lada hitam) are parts of the Piperaceae. One of the chemical constituents found in the fruit of the two plants is piperine, which has properties as antimicrobial, antidiabetic, anti-inflammatory, anticancer etc. This study aims to determine the piperine levels contained in 95% ethanol extract of java chili and black pepper fruits from regions with different altitude using UV-Visible spectrophotometer. Each sample were extracted by maceration method using 95% ethanol. Qualitative identification of piperine was carried out using thin layer chromatography (TLC). Determination of piperine levels was carried out with UV-Visible spectrophotometer at maximum wavelength of 253.8 nm. The results showed that the levels of piperine contained in the 95% ethanol extract of java chili fruit from low altitude (Lampung), medium altitude (Madura) and high altitude (Bogor) are 1.54±0.02%; 1.44±0.02%; and 1.41±0.02% (w/v), respectively. Whereas the levels of piperine contained in the 95% ethanol extract of black pepper fruit from low altitude (East Luwu), medium altitude (Central Lampung) and high altitude (Bogor) are 5.63±0.14%; 5.38±0.05%; and 4.87±0.09% (w/v), respectively.